Genetic diversity of Indian porcine circovirus type 2 (PCV2) isolates (2006-2018) - JOHN, J K; KATTOOR, J J; SETHI, M; TOMAR, N; DAS, T; SAIKUMAR, G (The Indian Journal of Animal Sciences, 2020)
Porcine circovirus type 2 (PCV2) is an emerging viral infection in swine population and results in severe economic loss to piggeries worldwide. The present study was conducted to explore the genetic diversity of PCV2 circulating in swine population of India from 2006–2018. A total of 74 heart, lungs, spleen and lymph nodes collected from different regions in Uttar Pradesh, India were subjected to molecular analysis. For studying genetic diversity, the complete nucleotide and ORF2 sequences of 95 PCV2 including 43 nucleotide sequences from India were used. DNA was extracted from samples and positive samples were subjected to full genome sequencing and phylogenetic analysis was done by maximum likelihood method. Phylogenetic analysis of 40 Indian PCV2 genomes downloaded from GenBank along with three new isolates from the current study based on the complete genome and cap gene together with nucleotide sequences of PCV2 isolates from different countries results in a tree in which Indian isolates clustered in 4 different branches includes PCV2b-1C, PCV2a-2D, PCV 2b-1A/B, PCV 2d-2 recombinant group and two new cluster in which one clustered along with unclassified PCV2 viruses from Indonesia and Croatia. The comparison of ORF2 gene among Indian isolates revealed nucleotide identity ranging from 88.6% to 99.6%, indicating the genetic diversity of PCV2 strains circulating in Indian pig. The present work reports for the first time in India the PCV2-1A/B cluster of 2b genotype and all the Indian isolates available in India from 2006–2018 were used in this analysis.